1204 Improving lymphatic function to reduce B cell responses in lupus. (14th December 2022) - Ambler, William G; Howlader, Mir; Chalasani, Madhavi Latha S; Seltzer, Ethan S; Sim, JiHyun; Shin, Jinyeon; Schwartz, Noa; Dasoveanu, Dragos; Carballo, Camila B; Sevim, Ecem; Siddique, Salma; Rodeo, Scott; et al.
Abstract : Background: In SLE, that ultraviolet radiation exposure can induce both photosensitive skin responses and increased autoantibody titers suggests a critical and targetable role for the communication from skin to draining lymph nodes in regulating lymph node B cell responses. Lymphatic vessels bring cells and signals from skin to draining lymph nodes to regulate immunity and dysfunction of lymphatic flow has the potential to alter immunity. Here we examine lymphatic flow function in SLE humans and models, showing that lymphatic flow from skin to lymph nodes is compromised. that improving lymphatic flow by manual lymphatic drainage (MLD) or in a transgenic model reduces lymph node B cell responses, and delineate the mechanistic underpinnings of how lymphatic flow modulates draining lymph node function. Methods: We examined lymphatic vessel luminal area considered to be reflective of lymphatic flow function in healthy controls, SLE, and control disease (anti-phospholipid antibody+ non-SLE patients) by immunohistochemistry and image analysis. We examined lymphatic function and performed manual lymphatic drainage in both MRL/lpr and imiquimod-induced lupus models. Lymphatic function was assessed by Evans blue tissue clearance assays and lymph node function was assessed by mainly by flow cytometry. Lymphatic flow was improved by either manual lymphatic drainage, adapted to mice based on techniques used in humans, or in a transgenic PTEN f/f Flt4-Cre ER model with increased lymphatic numbers and function. Results: SLE patient skin showed increased lymphatic vessel lumen size in skin and multiple SLE mouse models showed reduced clearance of intradermally-injected Evans blue, both suggesting reduced lymphatic flow in SLE. Improving lymphatic flow by manual lymphatic drainage (MLD) or in imiquimod-treated PTEN f/f Flt4-Cre ER mice reduced both cutaneous photosensitivity and lymph node germinal center and plasma cells. Mechanistically, improved flow restrains B cell responses by upregulating lymph node fibroblastic reticular cell CCL2, which modulates monocyte phenotype to limit germinal center and plasma cell numbers. Conclusions: Our results suggest a scenario whereby dysfunctional communication between the skin and the immune system alters lymph node function to modulate disease, point to a lymphatic flow-lymph node stromal axis as a therapeutic target, and suggest the possibility of manual lymphatic drainage, an existing treatment modality used in breast adjunctive treatment in SLE.